An investigation in the use of pressure mat to monitor turn performance in swimming - Cossor, J.; Slawson, S.; Chakravorti, N.; Mason, B.; Conway, P.; West, A. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
A purpose built pressure mat was designed and developed by Loughborough University in order to characterise the wall contact phase of swimming turns. In-house software enabled information concerning horizontal and vertical foot locations as well as orientation of the feet, wall contact time and peak force data that was extracted automatically. Two elite male swimmers on two separate days performed three maximal effort turns that resulted in similar values for wall contact time, peak pressure, as well as vertical and horizontal locations on the wall. Subject two produced greater peak forces (1.69 and 1.76BW) than subject one (1.34 and 1.20BW). Future testing will use larger subject numbers to obtain the statistical significance of the measured values.